2023
DOI: 10.3389/fimmu.2022.1062067
|View full text |Cite
|
Sign up to set email alerts
|

Robust humoral and cellular recall responses to AZD1222 attenuate breakthrough SARS-CoV-2 infection compared to unvaccinated

Abstract: BackgroundBreakthrough severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in coronavirus disease 2019 (COVID-19) vaccinees typically produces milder disease than infection in unvaccinated individuals.MethodsTo explore disease attenuation, we examined COVID-19 symptom burden and immuno-virologic responses to symptomatic SARS-CoV-2 infection in participants (AZD1222: n=177/17,617; placebo: n=203/8,528) from a 2:1 randomized, placebo-controlled, phase 3 study of two-dose primary series AZD1222… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Consistent with the primary analysis, our follow-up used standardized assays against ancestral SARS-CoV-2. Other studies of SARS-CoV-2 variant specific neutralizing antibody responses post-AZD1222 indicate responses against the Omicron variant are low following two-dose primary vaccination but increase after additional AZD1222 doses [14] , [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the primary analysis, our follow-up used standardized assays against ancestral SARS-CoV-2. Other studies of SARS-CoV-2 variant specific neutralizing antibody responses post-AZD1222 indicate responses against the Omicron variant are low following two-dose primary vaccination but increase after additional AZD1222 doses [14] , [15] .…”
Section: Discussionmentioning
confidence: 99%
“…This observation may provide additional insights into the potential association between breakthrough infections and the Delta and Omicron variants. Indeed, although some data revealed that 2 doses of the BNT162b2 or AstraZeneca vaccines have the same effectiveness against SARS-CoV-2 Alpha and Delta variants [ 33 ], other studies reported that individuals vaccinated with BNT162b2 are more protected than those vaccinated with AstraZeneca. In this context, an observational study, conducted in the United Kingdom, examined the effectiveness of 2-dose vaccines of either BNT162b2 or AstraZeneca, against infection with Alpha or Delta variants of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on the effectiveness of AZD1222 against hospitalisation are supported by clinical trial data demonstrating the durability of humoral and cellular immunity conferred by primary-series AZD1222 vaccination. 7 , 27 Sustained T-cell responses across SARS-CoV-2 variants have been shown to be important in conferring durable protection against severe disease. 28 …”
Section: Discussionmentioning
confidence: 99%